Новый вид поденок рода Ephemera (Ephemeroptera, Ephemeridae) из Армении - Клюге, Н.Ю. (Вестник зоологии, 1988)
phemera romantzovi sp. n. is described from a montane stream, Debed river basin, Akhpat village. The type material is deposited in Zoological Institute, USSR Academy of Sciences (Leningrad).